Analisis Politik Hukum dalam Perancangan Peraturan Perundang-Undangan Guna Mewujudkan Kepastian Hukum dan Keadilan Progresif - Nurlindawati Nurlindawati; Eko Purwanto; Ahmad Zaki Rayhan; Rendhi Renaldhi; Sena Neranda; Firman Adi Candra; Mochammad Ridzky Salatun (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
This paper aims to analyze the configuration of legal politics in the process of drafting regulations in Indonesia, particularly in the effort to synthesize the poles often considered conflicting: legal certainty and progressive justice. Using an analytical-critical approach, it is found that the legislative process is frequently trapped in political pragmatism that prioritizes legal certainty for economic interests, while neglecting responsive substantive justice. This paper proposes a synthesis where ideal legal politics must place humans as the primary subject of law, where formal certainty must not undermine substantive justice.